2015
DOI: 10.1175/jtech-d-14-00109.1
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of HF Radar–Derived Surface Currents Using Optimal Interpolation

Abstract: This study investigates the applicability of the optimal interpolation (OI) method proposed by Kim et al. for estimating ocean surface currents from high-frequency radar (HFR) in the northeastern Chukchi Sea, where HFR siting is dictated by power availability rather than optimal locations. Although the OI technique improves data coverage when compared to the conventional unweighted least squares fit (UWLS) method, biased solutions can emerge. The quality of the HFR velocity estimates derived by OI is controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…One‐dimensional radial surface currents, truebold-italicr, from each HFR were used to estimate two‐dimensional surface currents, truebold-italicu, following the optimal interpolation (OI) scheme of Kim et al (). Fang et al () investigated the performance of the OI method applied to the Chukchi HFR network. They used analytical stream functions to simulate spatially and temporally varying currents and found that for derived truebold-italicu with a normalized skill 0.7 (0–1 scale), errors were ∼2° angle shift and <0.1% magnitude variation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One‐dimensional radial surface currents, truebold-italicr, from each HFR were used to estimate two‐dimensional surface currents, truebold-italicu, following the optimal interpolation (OI) scheme of Kim et al (). Fang et al () investigated the performance of the OI method applied to the Chukchi HFR network. They used analytical stream functions to simulate spatially and temporally varying currents and found that for derived truebold-italicu with a normalized skill 0.7 (0–1 scale), errors were ∼2° angle shift and <0.1% magnitude variation.…”
Section: Methodsmentioning
confidence: 99%
“…The truebold-italicu were computed every cardinal hour, and the ROR at each grid point was determined. Fang et al () show that areas with 0.7 skill closely coincide to those with ROR < ∼5, thus grid points with ROR 5 were discarded. In addition, if the number of contributing truebold-italicr in the search radius (35 km) of the grid point was <20, the OI‐output truebold-italicu at the grid point was flagged.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…e TPS method does not need to set parameters, while other RBF needs to set parameters [23]. Some statistical-based methods (e.g., Kriging interpolation, optimal interpolation (OI), and Kalman filter) are conventional and classical methods in geoscience [12,13,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…This research effort identified the Chukchi Slope current-a subsurface current transporting Pacific-origin water westward over the upper continental slope-and quantified its seasonality [142,146,147]. Major surface current patterns in the northeastern Chukchi, and the wind conditions under which they occur, were derived and mapped [141,143]. The researchers also calculated the seasonal transport (and variations) at the head of Barrow Canyon [145].…”
Section: Field Observationsmentioning
confidence: 99%